(untitled) (Applied Biological Research, 2011)
The exploitation of pronounced heterosis in crosses between indica and japonica sub species of the Asian cultivated rice (Oryza sativa L.) has been limited by hybrid sterility, which has been recognized as one of the basis for speciation and genetic differentiation (Ouyang, 2009). Identification and use of WC genes (wide compatibility varieties) have been found effective in overcoming the hybrid sterility problem (Liu et al., 1996; Zhang et al., 1997). Inter-subspecific hybrids of rice have been developed since an early attempt in China (Yuan, 1994). Similar kind of attempt was made under temperate Kashmir conditions to get generate preliminary information about the genetic relatedness among different genotypes available at the germplasm base of RRRS, Khudwani. Moreover, the study was aimed to determine the role of genetic background of different genotypes for hybrid sterility and possible overcome using one WCV genotype.